"المعالجة المحاسبية لعمليات التامين –دراسة مقارنة بين المعيار الدولي 4 ونظام المحاسبي المالي- دراسة حالة : الشركة الوطنية للتامين وكالة جامعة (SAA-3305)" - محمد, علاق; سليم, شريف; فاطمة, حملاوي (University of eloued جامعة الوادي, 2021)
" هدف هذه الدراسة يتمثل في توضيح خصوصية المحاسبة المتعلقة بعمليات التامين، و هذا من خلال عرض أهم المفاهيم النظرية و التطبيقية المتعلقة بأنشطة التامين و كذا شركات التامين، كما و قد حاولنا إبراز أهمية تطبيق معيار الدولي لإعداد التقارير المالية IFRS4 في الصناعة التأمينية، خاصة في ظل إصداره عن مجلس المعايير المحاسبية، وكذا الإلمام بالجانب النظري حول النظام المحاسبي المالي SCF الخاص بهذا النوع من الشركات، ثم التطرق إلى أهم الحسابات و التسجيلات المحاسبية للعمليات المالية المتعلقة بها، مع إجراء دراسة مقارنة بين المعالجة المحاسبية لعمليات التامين من منظور معيار الإبلاغ المالي رقم 4 و النظام المحاسبي المالي. و توصلنا من خلال الدراسة الميدانية و التي طبقت في الشركة الوطنية للتامين وكالة جامعة إلى أن النظام المحاسبي المالي SCF يتلاءم مع طبيعة نشاط التامين، و خصوصية عمليات التامين بالشركة، بالرغم من تميز قطاع التامين بخصائص تشكل مفارقة يبنه و بين باقي القطاعات و الأنشطة المتبعة فيها، إلا أن النظام المحاسبي المالي ساعد في تنظيم المحاسبة في قطاع التامين بما يتلاءم مع خصوصيتها على الصعيد المحلي، لكنه واجه العديد من الصعوبات التي حالت دون التطبيق للمعيار و التي تتمثل في عدم توفر البيئة الاقتصادية الملائمة و المناسبة، لتطبيق هذا الأخير بالإضافة إلى تعقيد النظام المحاسبي المالي و عدم تماثله مع النظام الجبائي الجزائري. ""The aim of this study is to clarify the privacy of accounting related to insurance operations, and this by presenting the most important theoretical and applied concepts related to insurance activities as well as insurance companies, and we have tried to highlight the importance of applying the IFRS4 standard in the insurance industry, especially in light of The issuance of it by the Accounting Standards Board, as well as familiarity with the theoretical aspect about the financial accounting system SCF for this type of company, then touched upon the most important accounts and accounting records for the financial operations related to them, along with conducting a comparative study between the accounting treatment of insurance operations from the perspective of Financial Reporting Standard No. 4 And the financial accounting system. Through the field study that was applied in the National Insurance Company as a university agency, we concluded that the SCF financial accounting system is compatible with the nature of the insurance activity, and the specificity of the company’s insurance operations, despite the insurance sector’s distinctive characteristics that constitute a paradox between it and the rest of the sectors and activities followed in it. However, the financial accounting system helped organize accounting in the insurance sector in line with its specificity at the local level, but it faced many difficulties that prevented the application of the standard, which is the lack of an appropriate and appropriate economic environment for the application of the latter in addition to the complexity of the system Financial accounting and its inconsistency with the Algerian tax system. "
مذكرة ماستر تدقيق محاسبي
Keywords: عمليات التامين، شركات التامين، القيمة العادلة، محاسبة الظل، معيار الإبلاغ المالي الدولي رقم4، النظام المحاسبي المالي .; insurance operations, insurance companies, fair value, shadow accounting, International Financial Reporting Standard No. 4, financial accounting system.